1990
DOI: 10.1161/01.cir.82.6.1995
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal blood pressure response during exercise in hypertrophic cardiomyopathy.

Abstract: To investigate the incidence of abnormal exercise blood pressure responses in hypertrophic cardiomyopathy (HCM) and the potential role of hemodynamic instability as a mechanism of sudden death, 129 consecutive patients with HCM underwent maximal symptom-limited treadmill exercise testing with blood pressure recording. Four patterns of blood pressure response were observed. Forty-three patients had significant exercise hypotension, with either a continuous fall in systolic blood pressure (n=5) from the start of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
103
1
4

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 253 publications
(113 citation statements)
references
References 32 publications
5
103
1
4
Order By: Relevance
“…Frenneaux et al found that during exercise, the blood pressure fell in 33% of the HCM patients, and an abnormal blood pressure response during the recovery after exercise was observed in 23% of the patients. 5 These abnormal pressure responses are responsible for the poor prognosis of these patients, 7,8,13 and that they are frequently seen in young individuals with HCM. 5 However, it seems that these pressure depressions are independent of the increase in CO. 5 On the other hand, Lele, et al 14 reported that HCM patients show an insufficient increase in CO during exercise, as measured by equilibrium radionuclide ventriculography, and that the exercise capacity correlated with both the peak cardiac index 14,15 and peak stroke index.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Frenneaux et al found that during exercise, the blood pressure fell in 33% of the HCM patients, and an abnormal blood pressure response during the recovery after exercise was observed in 23% of the patients. 5 These abnormal pressure responses are responsible for the poor prognosis of these patients, 7,8,13 and that they are frequently seen in young individuals with HCM. 5 However, it seems that these pressure depressions are independent of the increase in CO. 5 On the other hand, Lele, et al 14 reported that HCM patients show an insufficient increase in CO during exercise, as measured by equilibrium radionuclide ventriculography, and that the exercise capacity correlated with both the peak cardiac index 14,15 and peak stroke index.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Despite the lack of an association with arrhythmias, 4 sudden cardiac death is more likely to occur in young patients than adult patients with HCM and the reason for this is unclear, although it was recently suggested that exercise-induced hypotension is related to sudden cardiac death in HCM patients. [5][6][7][8] The aim of the present study was to measure the cardiac output (CO) of young patients with HCM during exercise using impedance plethysmocardiography to elucidate the hemodynamic response of these patients to exercise.…”
mentioning
confidence: 99%
“…According to the previous reports, the mechanism of abnormal BPR was explained as follows: (1) An inappropriate fall in SVR caused by an excessive peripheral vasodilatation led to a centrally mediated reflex by ventricular baroreceptor stimulation, resulting in an inhibition of sympathetic tone in resistant vessels; 9,10,18 (2) there was an inappropriate increase in stroke volume due to impaired LV filling secondary to LV hypertrophy and tachycardia. 19 Olivotto et al speculated that the mechanism of abnormal BPR during exercise may be different according to the age; that is, abnormal BPR may reflect hemodynamic instability in young patients (< 50 years), while in older patients (≥ 50 years) it may simply reflect age-related cardiovascular changes that have little prognostic relevance.…”
Section: Hemodynamic Change In Patients With Abnormal Blood Pressure mentioning
confidence: 99%
“…[7][8][9] Furthermore, the literature suggests that abnormal BPR is caused by an inappropriate decrease in systemic vascular resistance (SVR), 9,10 and subendocardial ischemia. 11 On the other hand, we previously reported that some patients with nonobstructive HCM showed systolic dysfunction during exercise.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] The possible mechanisms responsible for these abnormalities are thought to include an abnormal decrease in systemic vascular resistance 3,4 and subendocardial ischemia. 5 We have reported previously that some patients with non-obstructive HCM show a decrease in ejection fraction (EF) during exercise.…”
mentioning
confidence: 99%